Pengaruh Suhu Penyimpanan dan Varietas terhadap Mutu Buah Tomat - Fitriani, Annisa; Tamrin, Tamrin; Rahmawati, Winda; Kuncoro, Sapto (Jurnal Agricultural Biosystem Engineering, 2022)
Tomato is agricultural commodities which very easy to be damaged after the Harvest.  These things happened caused of the handle at the Harvest time which done by the farmer is not exactly right especially in keeping the quality of the tomato.  The purpose of this research is for knowing the influence of the tomatoes quality and the influence varieties for quality of tomatoes during storage period.  This research used design of Rancangan Acak Lengkap (RAL) Factorial, the first factor is varieties, tomato varieties used are ordinary tomatoes, Rampai Tomatoes, and Ceri Tomatoes.  The second factor is temperature (temperature 10°C, 20°C and room temperature).  Observations made are changes in weight loss, violence, total solved solids, water content and vitamin C.  The experiment was carried about 3 times. The result of this research show that the storage temperature significant effect on weight lost and statistically significant effect on hardness and total dissolved solids during the storage period, but the temperature storage not effect on Vitamin C levels, moisture content. Tomatoes variety effect on weight loss, level of violence, total dissolved solids, water content and vitamin c levels.  The best temperature used to maintain quality and extend the shelf life of tomatoes is at the storage temperature of 20°C. Keywords: Temperature, Total Dissolved Solids, Variety, Vitamin C, Weight Loss.